Fixed Point Approximation of Monotone Nonexpansive Mappings in Hyperbolic Spaces - Amna Kalsoom; Naeem Saleem; Hüseyin Işık; Tareq M. Al-Shami; Amna Bibi; Hafsa Khan (Journal of Function Spaces)
Fixed points of monotone α-nonexpansive and generalized β-nonexpansive mappings have been approximated in Banach space. Our purpose is to approximate the fixed points for the above mappings in hyperbolic space. We prove the existence and convergence results using some iteration processes.